A multi‐isotope, multi‐tissue study of colonial origins and diet in New Zealand. Issue 4 (18th May 2020) - King, Charlotte L.; Buckley, Hallie R.; Petchey, Peter; Kinaston, Rebecca; Millard, Andrew; Zech, Jana; Roberts, Patrick; Matisoo‐Smith, Elizabeth; Nowell, Geoff; Gröcke, Darren R.
Abstract: Objectives: Colonial period New Zealand was lauded as a land of plenty, where colonists could improve their station in life and secure a future for their families. Our understanding of colonial experience, however, is often shaped by historical records which communicate a state‐sponsored version of history. This study aims to reconstruct the lives of settlers using isotopic evidence from the colonial skeletons themselves. Materials and methods: We use skeletal remains from recently excavated colonial sites in Otago (South Island, New Zealand) to illustrate the information that can be gleaned from the isotopic analysis of individuals. We use 87 Sr/ 86 Sr to identify European settlers, and δ 13 C and δ 15 N from collagen and hair keratin, as well as dental enamel carbonate δ 13 C to trace dietary change over their life‐courses. Results: Strontium isotope analysis shows that all adults in our sample are non‐local. Dietary isotopes show that while most individuals had relatively consistent childhood diet, one individual with more rural origins likely had seasonal use of resources during childhood. While some members of the population seem to have increased their meat intake in the new colony most do not have clear evidence for this. Discussion: We show the diversity of human experience in first‐generation New Zealanders both prior to emigration and in the new colony. Despite colonial propaganda claiming that circumstances in New Zealand were improved for all settlers, we have little evidence for this, aside from among individuals of potentially high status.